Arabic Learning and Religious Identity among Non-Muslim Students in Indonesia - Nasution, Sahkholid; Asari, Hasan; Al-Rasyid, Harun; Faridah, Faridah; Zulpina, Zulpina; Rangkuti, Rafiqa Ulfah; Kawaid, A Irwan Santeri Doll (Jurnal Ilmiah Peuradeun, 2025)
The Arabic language is often perceived by some individuals as inherently tied to Islamic teachings, creating a misconception that deters non-Muslims from engaging with it academically. This study addressed this issue by exploring how non-Muslim students constructed their religious identity and developed adaptation strategies while learning Arabic at State Islamic Religious Universities in Indonesia. The research employed a qualitative phenomenological approach, collecting data through in-depth interviews with five Christian students at the State Islamic University of North Sumatra in Medan, and analyzing it using the ATLAS.ti application. The findings revealed that students maintained a strong and unaffected sense of religious identity, as they viewed Arabic not as a spiritual language but as a neutral, international means of communication. Participants adopted various adaptation strategies, such as framing Arabic as knowledge rather than belief, engaging in conformity, experiencing minority privilege, employing peer learning, utilizing environmental resources for knowledge, and reinforcing religious practices within the family. These strategies highlight the dynamic interplay between identity, belief, and academic engagement in a religious educational context, offering new insights into inclusive language learning environments in Islamic institutions.